8) 7+[12–(6-4)]
h) 18 - [14 – (6-2)]
i) 8–2– [6-(3-2)]repede va rog mă ajutati
Răspunsuri la întrebare
Răspuns de
0
Răspuns:
7+(12-2)=
7+10=17
18-(14-4)=
18-10=8
6-(6-1)=
6-5=1
Răspuns de
0
Răspuns:
7+[12-(6-4)]=7+(12-2)=7+10=17
18-[14-(6-2)]=18-(14-4)=18-10=8
8-2-[6-(3-2)]=8-2-(6-1)=8-2-5=8-7=1
Alte întrebări interesante
Biologie,
8 ani în urmă
Limba română,
8 ani în urmă
Limba română,
8 ani în urmă
Matematică,
8 ani în urmă
Franceza,
8 ani în urmă
Limba română,
9 ani în urmă
Limba română,
9 ani în urmă